2017
DOI: 10.2174/1389557516666160219123222
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine to Deal With Cancer Cell Biology in Multi-Drug Resistance

Abstract: Today Cancer still remains a major cause of mortality and death worldwide, in humans. Chemotherapy, a key treatment strategy in cancer, has significant hurdles such as the occurrence of chemoresistance in cancer, which is inherent unresponsiveness or acquired upon exposure to chemotherapeutics. The resistance of cancer cells to an antineoplastic agent accompanied to other chemotherapeutic drugs with different structures and mechanisms of action called multi-drug resistance (MDR) plays an important role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Overall, tumor cells of different colonies can be more sensible to chemotherapy agents. Although, proliferative tumor cells in a continuous exponential phase, are more susceptible to drugs [39]. The results showed that, the effect of the combination of LabMol-12 and oxaliplatin is more effective when the cells have a proliferative capacity.…”
Section: Discussionmentioning
confidence: 97%
“…Overall, tumor cells of different colonies can be more sensible to chemotherapy agents. Although, proliferative tumor cells in a continuous exponential phase, are more susceptible to drugs [39]. The results showed that, the effect of the combination of LabMol-12 and oxaliplatin is more effective when the cells have a proliferative capacity.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, developing nanomedicine applications in the future will need knowledge of the molecular fingerprints of illness. [40] More study is needed to increase the application of nanomedicine beyond what has been stated in review employing the currently existing nanoprobes and nanotheranostics devices.…”
Section: Opportunities and Difficulties For The Futurementioning
confidence: 99%
“…Both MRP1 and P-gp are members of the superfamily of ATP-binding cassette transporters, which is involved in multidrug resistance. The increased expression of MRP1 and P-gp usually represents the enhancement of multidrug resistance (20). Therefore, the results of the present study suggest that LINC00707 knockdown enhances DDP sensitivity by weakening multidrug resistance.…”
Section: Discussionmentioning
confidence: 51%